ARCA-ARCA DARI CANDI TONDOWONGSO DAN CANDI GURAH, KEDIRI - Lisa Ekawati (Balai Arkeologi Yogyakarta, 2008)
Gurah district which located at Kediri region is very rich in term of archaeological heritage. Lot of statues and brick structures were found at Tondowongso and Tiru Lor area. The most interesting thing is the discovery of Brahmā, Candra, Sūrya, Nandi and Yoni statues. In term of iconography, every statue from both areas shows similarity as well as differences. By comparing the composition of the statues found at Gurah temple, it could be presumed that the statues were made in the same place as the ones found in Tondowongso. The research at Tondowongso has not finished yet,so this assumption still need to be re-examined.